Design, Fabrication, Construction, and Cost Assessment of Virginia's First Corrosion Resistant ASTM A1010 Plate Girder Bridge. Issue 26 (December 2018) - Sharp, Stephen R.; Provines, Jason; Moruza, Audrey K.; Via, William F.; Harrop, Keith N.
This study documents the construction of the Waynesboro Route 340 Bridge with low-maintenance corrosion resistant steel girders, cross-frames, and stainless steel bolts. This includes documenting the fabrication of the ASTM A1010 steel plate, girder and secondary members, erecting the girders, and completion of the construction process. The types of stainless steel materials used to fabricate the girders are reported with a comparison to traditional materials. Information on the material properties was documented. Cost analysis was performed and guidance was provided to the Virginia Department of Transportation (VDOT) about how this type of plate girder will benefit the DOT. Overall, the design, fabrication, and construction of the A1010 steel girder Route 340 bridge was a success. This is the first bridge in the United States to use A1010 haunched girders, completely stainless steel bolted splices, and A1010 cross frames. To that end, it was concluded that a conventional steel bridge fabricator can successfully fabricate an A1010 steel bridge. Through detailed testing of the stainless steel bolts, it was also shown that acceptable utilization of stainless steel structural connections can be achieved. VDOT was also able to successfully demonstrate fabrication of A1010 steel cross frames utilizing bent plate shapes. It is recommended to continue to evaluate improved welding processes for the A1010 base metal and to consider the use of A1010 as a repair material for in-service structures located in corrosive macro-environments, such as near saltwater or industrial sites, or those which contain aggressive micro-environments such as steel beam ends under joints.